x4-1=x6+9

Simple and best practice solution for x4-1=x6+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x4-1=x6+9 equation:



x4-1=x6+9
We move all terms to the left:
x4-1-(x6+9)=0
We add all the numbers together, and all the variables
-(+x^6+9)+x4-1=0
We add all the numbers together, and all the variables
x^4-(+x^6+9)-1=0
We get rid of parentheses
x^4-x^6-9-1=0
We do not support expression: x^4

See similar equations:

| x−5/6=1 | | 6n-9n+10n/12=21 | | X^3+2x^2+8x+64=0 | | x*58=76 | | 40=31x | | x*78=76 | | y–1=9 | | X^3*(2x-6)=0 | | 9x–2x=–42 | | Ax13=20 | | 3^x(5^2x)=6(2^x) | | 2t^2+4t+384=0 | | 2w+3w+6=46 | | 4(x-5)+3=-1 | | (7-4y^2)=0 | | 2670=30k | | 5x(2x+7)=3x+4 | | 8+7y/2+3y=8 | | y+8=34 | | 4x^3+18x-7=0 | | 4x^3+18x-1=0 | | 84-6x=24 | | 1/2v+7=19 | | Y=0.6x+1500 | | 47×x=93+15 | | 5/2n=5/10 | | N=5+6n-6 | | -16.5=3.3x | | 301=5+6n-6 | | 3x^2-18x+96=0 | | 1/2x10=50 | | x^2(x+7)=1/2(14^2+16) |

Equations solver categories